Interpreting the Meaning of Lyrics and Music Video of "Sorai" by Nadin Amizah Based on Ferdinand de Saussure’s Theory - Ristama Fitri Widia Hutabalian; Lyra Hani Chintya Manullang; Elizabeth Hutapea; Jesica Geraldine Sibagariang (SMASH: Journal of Social Management Sains and Health, 2025)
This study examines the interplay of lyrical and visual symbolism in Nadin Amizah’s Sorai through the lens of Ferdinand de Saussure’s semiotic theory. By analyzing the song’s lyrics and music video as multimodal texts, the research explores how linguistic and visual signifiers construct themes of interdependence, emotional burden, and acceptance of impermanence. Utilizing Saussure’s dyadic model of signifier-signified relationships, the analysis reveals that natural metaphors (e.g., sky, sea) and cultural lexicon (e.g., sorai, derived from Minangkabau) function as arbitrated codes to convey existential narratives. The lyrics emphasize emotional restraint and transience, while the music video amplifies these themes through chromatic symbolism, spatial binaries, and gestures of unattainable connection. Despite alignment in thematic exploration, the video diverges by universalizing impermanence through abstract visuals like tombstones and desaturated landscapes. The findings highlight the necessity of contextualizing Saussurean semiotics within cultural frameworks, particularly in non-Western artistic expressions, and demonstrate the dynamic role of multimodal analysis in deciphering layered meanings. This study contributes to broader discussions on the applicability of classical semiotics in contemporary media and underscores the interplay between regional idioms and universal human experiences.